Blowing the Bubble: The Global Funding of the Irish Credit Boom - Everett, Mary M. (Economic & Social Studies, 2015)
European global banks played a significant role in the international transmission of liquidity during the period prior to the global financial crisis. This paper examines how European global banks channelled finance, raised in US wholesale funding markets, via cross-border banking flows to Irish retail banks during the first decade of the euro. The results indicate that global factors, namely the US-sourced funding of European global banks and global risk, were influential in driving cross-border banking inflows to Ireland. Furthermore, the empirical analysis suggests these global factors contributed to changes in domestic private non-financial sector credit during the Irish credit boom. These results shed new light on the factors influencing the international funding of Irish retail banks and changes in domestic credit during the credit boom.